«ОЛИЙ НЕРВ ФАОЛИЯТИ ВА УНИНГ ЁШГА ОИД ХУСУСИЯТЛАРИ» МОДУЛИНИ ЎҚИТИШДА «БИРГАЛИКДА ЎҚИЙМИЗ» МЕТОДИДАН ФОЙДАЛАНИШ - Палўанова, Г.; Марасулова, Д. (SCIENCE and SOCIETY, 2019)
Through collaborative learning, students learn do read together the task. This technology encourages students to pursue creative research. Carrying out tasks completely they try to achieve the goal of integrating the learning material and achieving the intended goals.At the same time, students are able to find a solution to the problem and to work in the team.
Keywords: nervous system; reflex; temperament; dynamic stereotype; neurosis; distress; stress